Tinjauan Hukum Islam Dan Hukum Positif Terhadap Investasi Berskema Ponzi - Ani, Qur'aini Safitri; Wulandari, Diah Dwi; Faizal, Liky (ASAS, 2022)
The purpose of the research in this article is to analyze the investment system with Ponzi schemes and the views of Islamic law on the practice.  The focus of the research is how the system and Islamic law view investments with Ponzi schemes. The type of research is the library where the source of the data takes from books, journals, documents, and scientific research/writing. The procedure for collecting data for the research is the Fatwa of the Sharia Council No. 20/DSN-MUI/IV/2001 and UU no. 7 of 2014. The study is an analytical description that uses qualitative data analysis techniques with a deductive approach.  Based on the research results, it can be concluded that investment with a Ponzi scheme offers high profits so people are interested in investing by asking them for an initial payment in a form of an administrative fee. Then the money will be circulated to pay other members affecting new members' losses. This system will continue to rotate until no more members join. In Islamic law, this investment is prohibited and unlawful because it contains elements of gharar and najsy (false offers), bai al-ma'dum (selling goods that do not yet exist), and insider trading (spreading misleading information). Whereas in positive law this investment is declared illegal because there is an element of fraud with the pyramid concept as contained in Law no. 7 of 2014 concerning trade. Keywords: Islamic Law, Positive Law, Investment, Ponzi Scheme